Heritability estimates of first lactation 300-day milk yield under single versus multi-trait animal models in Phule Triveni cattle - AMBHORE, G S; SINGH, AVTAR; DEOKAR, D K; SAHOO, S K; SINGH, MANVENDRA; DIVYA, P (The Indian Journal of Animal Sciences, 2016)
First lactation records of 493 Phule Triveni cows sired by 55 bulls on production traits, viz. first lactation 300- day or less milk yield (FL300DMY), first lactation length (FLL), first dry period (FDP) and reproduction traits like age at first calving (AFC), first calving interval (FCI) and first service period (FSP) were used to compare the heritability estimates of FL300DMY under single-trait animal model (ST-AM) versus multi-trait animal models (MT-AM) in Phule Triveni cattle. Under two-trait models, the heritability estimate was found to be highest in FL300DMY-AFC combination as 0.34 ± 0.14. Under three-trait models, the heritability estimate was highest (0.33 ± 0.14) in FL300DMY- AFC- FDP combination. Under four-trait models, the highest estimate of heritability (0.53 ± 0.12) was in FL300DMY-FLL-AFC-FCI combination. Comparison of heritability estimates of FL300DMY from different models revealed that the estimates were varying from single to multiple traits in different combinations. The lowest residual variance (190566) and highest heritability (0.53 ± 0.12) of four-trait combination FL300DMY- FLL-AFC-FCI indicated that this four-trait combination should be used for selection of Phule Triveni cows.